Peningkatan Kualitas Pembelajaran Pendidikan Pancasila di Lembaga Pendidikan Tenaga Kependidikan - Maman Rachman (Universitas Negeri Malang, 2016)
This action research was conducted in two cycles within 12 months. The phase in each cycle contains planning, action, observation and reflection. The result indicates that for enhancing the quality of Pendidikan Pancasila instruction, some actions have to be done. Instructional design should be informative and communicative; methods and media should vary; the learning-teaching process should be attractive; materials presentation should be integrated, contextual and controversial; exercises should be challenging; and evaluation should be comprehensive. The recommendation suggested by researcher is that the lecturers have to possess the firm insight of learning-teaching strategy and the ability to develop learning-teaching plan